Manajemen pemasaran : teori & aplikasi dalam bisnis / Andriasan Sudarso, Lili Suryati, Wilhelmus Hary Susilo ; editor Erang Risanto. - ANDRIASAN SUDARSO, 1968-; Lili Suryati; Wilhelmus Hary Susilo; Erang Risanto (Andi, 2015)
x, 286 hlm. : ilus. ; 23 cm